Digital Activism in the COVID-19 era - Olga Anaid Diaz Jacinto; Cruz García Lirios (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The exploration of the dimensions of digital activism was the objective of this work. A non-experimental study was carried out with a non-probabilistic selection of 150 students, considering their affiliation with student organizations. A four-dimensional structure was established; technological habitus, computational self-efficacy, diffusion of innovations and Internet mobilization that explained 48% of the total variance, although the design limited the results to the research scenario, suggesting the extension of the study and the inclusion of variables such as training, socialization and intention to use the devices and networks